Design and Development of a Low Cost Pulse Oximeter. Issue 1 (February 2021) - Naeem, Zain Hassan; Youseffi, Mansour; Sefat, Farshid; Khaghani, Seyed Ali; Raja, Tehmeena Israr; Patel, Arif; Javid, Farideh; Abdul Jamil, Muhammad Mahadi; Abd Wahab, Mohd Helmy
Abstract: There are various types of pulse oximeters (POs) including 'reflectance POs', which can be used on more sites like the forehead, chest or cheeks and work the same way as 'transmission POs' which is the most commonly used device for the continuous measurement of % blood oxygen saturation and pulse/heart rate. This paper describe the design and development of a low cost pulse oximeter (PO) specifically focused on the use of 'Reflectance Photo-Plethysmo-Graphy' (RPPG) technology, and compare with commonly used pulse oximeter devices at the East Lancashire Hospitals. The design arrangement involved the use of an Arduino Mega 2560 Circuit Board as microcontroller, Pulse Sensor, Light Emitting Diodes (LEDs) and Liquid Crystal Display (LCD), which allowed subsidising to make a functional device for accurate readings of Heart Rate (HR) in beats per minute (BPM) and % Blood Oxygen Saturation (SpO2). RPPG technique was successfully implemented within the design and development of the PO prototype, contrasting against the more conventional method of transmission pulse oximetry for obtaining HR and SpO2 values. It is concluded that the RPPG pulse oximeter is a more cost effective method of operation with comparable results.